АВТОМАТНАЯ МОДЕЛЬ ПОВЕДЕНИЯ ТИРИСТОРНОГО КЛЮЧА - Алымов, О.П.; Кулешов, Ю.Е.; Головко, А.А. (Інститут електродинаміки НАН України, Київ, 2012)
The automatic model of behaviour thyristor a switch which all components are set obviously is synthesised, and allowing to formalize logic synthesis of a digital control system of the electric converter with its subsequent realisation or on the basis of microprocessor means, or programmed means of creation of digital technics (SPLD, CPLD, FPGA, SoC, SoPC). References 10, table 1, figures 5.